Foreign direct investment in transition economies: the regional structure and peculiarities of development in Belarus - Pirozhnik, Ivan (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
The spatial structure of the world economy is divided into countries of economic center,semi-periphery and periphery. Changes of the spatial structure of the world economy and globalizationtrends are marked. A key element of the growing of globalization process is foreign direct investment(FDI) and activities of transnational corporations. Declining trend in foreign direct investmentis marked in conditions of instability of world economic development, shifts in FDI regional structureand their impact on countries with developing market economies. On the basis of the regional monitoringof the foreign direct investment the CIS market is described, in particular of the countries ofthe Customs Union and Belarus. The volumes of the Belarusian direct investment abroad are outlined,the forms of presence in foreign markets are indicated, the development of the commodity distributionnetworks, created by Belarusian enterprises and geography of inflow and outflow of FDI, is analyzed.The directions of improving the investment climate in Belarus and improve its position in the worldrankings are marked.